ANALISIS ZONA SELAMAT SEKOLAH (ZoSS) DI KECAMATAN DENPASAR SELATAN (STUDI KASUS: SDN 5 PEDUNGAN DAN SEKOLAH HARAPAN) - I Made Kariyana; I Komang Alit Astrawan Putra; I Nyoman Arta Wijaya (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2020)
SDN 5 Pedungan and Harapan School are schools in South Denpasar District which already have School Safety Zone (SSZ) facilities. The two schools are traversed by a fairly high traffic volume due to the large number of trip generation centers located along the road such as traders, education, and industry. This study aims to analyze the level of effectiveness of SSZ in both schools through which the traffic volume is quite high compared to other schools. The field survey was carried out by recording the vehicle travel time when crossing ZoSS at a distance of 100 m. The effectiveness level of SSZ was analyzed using Regulation of the Director General of Land Transportation in 2006, 2014, and 2018. The results of the analysis showed that the application of SSZ in South Denpasar District was not effective, the average percentage of vehicles compliant when crossing SSZ for SDN 5 Pedungan was 42.67%, which means that SSZ is quite effective and Hope School is 32.34% which means SSZ is less effective.